Faktor-Faktor yang mempengaruhi Kinerja Pemerintah Desa dimediasi oleh Pengelolaan Dana Desa - Afri Anton; Taufeni Taufik; Ruhul Fitrios; Yesi Mutia Basri (Politeknik Ganesha Medan, 2023)
This study aims to find empirical evidence of the Influence of Village Official Competence, Organizational Commitment and Transparency on Village Government Performance with Village Fund Management as a Mediator. This research was conducted at Village Government Officials in Padang Pariaman Regency. The sampling technique uses the census method by sending questionnaires to Village Government Officials. Of the 309 questionnaires distributed, 288 questionnaires were processed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis. The results of the research prove that there is an influence of Village Official Competence, Organizational Commitment and Transparency on Village Government Performance and Village Fund Management which is able to mediate the variables of Village Official Competency, Organizational Commitment and Transparency on Village Government Performance of Village Government Officials in Padang Pariaman Regency. By having qualified & competent Village Officials, the implementation of Village Fund Management can run well & smoothly (starting from planning, implementation, administration, reporting to accountability). Transparency as openness of public information has a very important role in increasing public participation, if there is public involvement in controlling & supervising the implementation of regional government then the performance produced by the government will run well. Good Village Fund Management can influence Village Government Performance, where the better the rules implemented by village officials, the better the Village Government Performance will be.